P238 Training opportunities in thoracic ultrasound for respiratory registrars – are current guidelines user friendly?. (15th November 2017) - Stanton, AE; Evison, M; Roberts, M; Latham, J; Clive, A; Battala-Duran, E; Bhatnagar, R; Asciak, R; Diggins, B; Bintcliffe, O; Lees, D; Parsonage, M; et al.
Abstract : Introduction: Acquiring competency in thoracic ultrasound (USS) is mandatory for all respiratory trainees by the end of ST5, but it is often challenging for trainees to meet the requirements in current RCR guidelines for level 1 competency (≥1 session/week over≥three months, with 5 scans per session performed by trainee). We aimed to clarify where thoracic ultrasound training opportunities currently exist for respiratory registrars to inform further debate around the competency framework. Methods: Trainees in the South west, North West and Oxford deaneries were invited to submit data on numbers of thoracic USS performed by both radiology departments (specifying numbers of scans per morning/afternoon session) and respiratory teams (specifying pleural clinic/procedure list/respiratory ward/other ward or clinic) over a randomly selected 4 week period between January and May 2017. Data was to represent total number of scans performed within each department, not number of scans done by one individual. Results: Data was provided from 14 hospitals (6 South West, 7 North West, 1 Oxford) including 3 tertiary pleural centres. Results are shown in Table 1 . Full Results from 2 centres represent estimated numbers and one site (North Manchester) submitted 3 weeks data. There was no radiology session in any hospital with ≥5 thoracic ultrasound sans performed (out of total of 55 weeks sampled across all sites). Conclusions: In almost all surveyed hospitals from two deaneries, and a tertiary centre from a third, the majority of thoracic ultrasound is performed by respiratory teams rather than radiologists and in a variety of elective and unscheduled situations. Similarly the principle opportunity for USS training exists within the respiratory team and is deliverable out-with the tertiary setting. The currently recommended exposure of regularly attending a list or session to undertake 5 USS is not achievable in radiology departments even where thoracic USS is being performed, including surveyed tertiary pleural centres. Future recommendations on USS training requirements for respiratory trainees need to be flexible to take account of where opportunities exist and should recognise the role that both radiology and respiratory teams provide.